Compassion, ethics of care and legal rights - Herring, J (Cambridge University Press, 2017)
This paper will explore the difficulties facing law in promoting compassion and responding to caring relationships. These include the difficulties in determining whether a person has demonstrated compassion and in enforcing any legal requirement for compassion. The paper will use the ethics-of-care literature to critique two key legal tools: human rights and the concept of best interests. These concepts are typically designed to promote individualistic abstract understandings of the self, which are problematic when used in the setting of intimate relationships. However, this paper will suggest that it might not be necessary to abandon the concepts of rights and best interests. They may be useful for setting the boundaries for a space in which appropriate care and compassion can be exercised. It will also be suggested that both rights and best interests are not immune from a relational analysis and might, with appropriate modification, be used to promote the exercise of compassionate relational care.